(untitled) (Biological Sciences - PJSIR, 2024)
Raw milk is recognized as a complete diet and have high food values and supplies nutrients like water, proteins, lactose, fat, carbohydrates, vitamins etc. Animal-source food pays a very impressive part in poverty reduction, nutritional improvement, food security and health in developing countries. Pakistan is rated as one of the leading milk producer country in the world. Over 8 million rural families are directly engaged in livestock production and secure above 30-40% of their annual earnings. Over the year livestock has emerged as the biggest sub-sector in agriculture as it contribute 60.1% to the agriculture value addition and 11.5% to the GDP during FY2021, while milk producing animals are underfed situation. In Pakistan, 80% milk is produced at the small scale in rural area, 15% in peri-urban and only 5% in the urban areas. It is estimated that 97% milk is marketed in raw form and rest is processed. The milk production and distribution systems are outdated and un-organized, the whole setup is controlled by the informal private sectors. Different hazardous contamination incorporate into the dairy chain during milk production, processing, transportation, storage and serving that may affect milk quality profile. Milk contamination occurs by endogenous and exogenous contamination sources. Unhygienic practices of milk handling from farms to table promotes the chance of pathogenic microbial contamination which terribly affect its composition, quality and shelf life. Adulteration in the raw milk is the main problem in Pakistan. Food related diseases are quite common in Pakistan and different approaches like unhealthy conditions and absence of food standards, unhygienic and inadequate sanitation, poverty and illiteracy are the certain root causes in spreading of these diseases. During the milk supply chain different hurdles like, lack of chilling system, inadequate transportation infrastructure and untrained staff are the core issues related to Pakistan dairy sector. Dairy staff are usually uneducated and resistant to anti-traditional practices. Quality has become the most important feature in almost all stages from farm to table. Therefore, trainings and skill development programs for dairy staff can ensure the quality milk production by utilizing the latest technology.